P30 Effects of carnitine supplementation in the type 1 diabetic heart: an in vivo hyperpolarized mrs study. (21st March 2018) - Savic, Dragana; Timm, Kerstin; Ball, Vicky; Heather, Lisa; Tyler, Damian
Abstract : Carnitine transports long-chain fatty acids across the mitochondrial membrane for subsequent β-oxidation. It is known that carnitine levels are decreased in cardiac diseases, such as diabetes, and that carnitine supplementation can have cardioprotective effects. The purpose of this study was to investigate the effects of l-carnitine supplementation on cardiac metabolism in the diabetic rat heart. Type 1 diabetic rats were generated by streptozotocin injection, control rats were injected with citrate buffer and all were treated for 3 weeks with daily injections of either l-carnitine or saline, where after they were subjected to CINE-MRI and hyperpolarized MRS. Blood glucose levels were elevated in both diabetic groups, with the saline treated diabetic group showing a progressive increase in hyperglycaemia. Hyperpolarized MRS demonstrated reduction of pyruvate dehydrogenase (PDH) flux in the diabetic groups, but PDH flux was significantly higher in the l-carnitine treated diabetic group. Both lactate and alanine were significantly elevated in the animals treated with l-carnitine. l-carnitine supplementation stabilises hyperglycaemia and increases the metabolism of pyruvate in the diabetic heart. l-carnitine provides a means to improve pyruvate metabolism in the diabetic heart.